Billion dollar whale the man who fooled Wall Street, Hollywood, and the world - Hope, Bradley; Wright, Tom (Hachette Books, 2018)
Two Pulitzer-finalist Wall Street Journal reporters document the true story of how a young social climber orchestrated one of history's biggest financial heists, exposing the secret nexus of elite wealth, banking, Hollywood and politics.